2020
DOI: 10.1016/j.cub.2020.03.070
|View full text |Cite
|
Sign up to set email alerts
|

CLASP Mediates Microtubule Repair by Restricting Lattice Damage and Regulating Tubulin Incorporation

Abstract: Highlights d CLASP stabilizes damaged microtubule lattices d CLASP converts partial protofilament assemblies into complete tubes d CLASP promotes complete repair of microtubule lattice defects d CLASP inhibits softening of microtubules bent by hydrodynamic flow

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 35 publications
4
65
0
2
Order By: Relevance
“…These damage sites get repaired by incorporating GTP-tubulin. Some proteins have recently been reported to cause tubulin dissociation from the shaft or to mediate GTP-tubulin incorporation (Vemu et al, 2018; Triclin et al, 2018; Aher et al, 2020;). At a GTP-tubulin incorporation site, depolymerizing microtubules can be rescued and start re-growing.…”
Section: Introductionmentioning
confidence: 99%
“…These damage sites get repaired by incorporating GTP-tubulin. Some proteins have recently been reported to cause tubulin dissociation from the shaft or to mediate GTP-tubulin incorporation (Vemu et al, 2018; Triclin et al, 2018; Aher et al, 2020;). At a GTP-tubulin incorporation site, depolymerizing microtubules can be rescued and start re-growing.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, MTs undergo polymerisation in the absence of enzymatic catalysis, but the addition of factors such as CLASPs, stathmins, tau, Eb proteins or XMAP215 can enhance and refine the process (Aher, Rai et al, 2020, Al-Bassam, Kim et al, 2010, Brouhard, Stear et al, 2008, Drechsel, Hyman et al, 1992, Li, Moriwaki et al, 2012, Manna, Thrower et al, 2009, Zanic, Widlund et al, 2013. Accordingly, many candidate regulators have been proposed in the literature to regulate MT polymerisation in axons, comprising factors that are MT plus endassociating, MT shaft-binding or involved in tubulin provision (summarised in (Voelzmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…MT polymerisation is primarily understood in vitro , where MTs can undergo polymerisation in the presence of nucleation seeds and tubulin heterodimers; the addition of catalytic factors such as CLASPs, stathmins, tau, Eb proteins or XMAP215 can enhance and refine the process (Aher et al , 2020; Al-Bassam et al , 2010; Brouhard et al , 2008; Drechsel et al , 1992; Li et al , 2012; Manna et al , 2009; Zanic et al , 2013). However, we do not know whether mechanisms observed in reconstitution assays are biologically relevant in the context of axons (Voelzmann et al ., 2016), especially when considering that none of the above-mentioned factors has genetic links to human neurological disorders on OMIM® (Online Mendelian Inheritance in Man), except Tau/MAPT which executes numerous disease-relevant functions also when detached from MTs (Morris et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, Coombes et al 52 presented evidence that the taper evolves during microtubule growth from a seed and reaches a steady-state length that varies with the free tubulin concentration. This approach has been extended to show that microtubule plus tips are elongated in cells and when microtubules are grown in vitro in the presence of regulatory proteins 11,54,55 . However, using similar approaches, Maurer et al 20 concluded that taper lengths for microtubules grown under standard conditions in vitro were below the detection limit of $180 nm for this technique, which they established using model convolution.…”
Section: Tapered Microtubulesmentioning
confidence: 99%